Comparism between phospholipase activity in (Candida albicans) by use two substrates (lecithin, L-a-phosphatidyl inositol) - M .A .Aouda, M .A .; S .S Herneem, S .S; M .1.Aboud, M .1. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Comparative study on tb.e activity of phospholipase enzyme which is produced by yeastØ¢  cum/ida albicansØ¢  Ø¢ into different culture media that contain phospholipids as substrates. The agar containing substrate (L-aØ¢Â phosphatidyl inositol) was used .The agar containing lecithin as other substrate for comparision was alsoused.The second culture media was found the best for enzyme activity whichwas measured by precipitation zone .